Anti-phase Variation of Hydrology and In-Phase Carbon Accumulations in Two Wetlands in Southern and Northern China Since the Last Deglaciation - Yu, Xuefeng; Chen, Jiquan; Zheng, Yanhong; Zhong, Wei; Ouyang, Zutao; Zhou, Weijian (Frontiers in Earth Science, 2020)
To examine the spatial patterns of hydrological variations in the southern and northern East Asia Monsoonal (EAM) region on millennial time scales, as well as to investigate the relationship between hydrological changes and carbon accumulation in these regions with contrasting environmental backgrounds, we performed facies-based hydrological reconstructions in two wetlands, Midiwan wetland (37°39′N, 108°37′E) and Dahu wetland (24°45′N, 115°2′E), located in a semi-arid loess-desert transitional zone and humid southern China, respectively. Our reconstructions revealed an anti-phase pattern of the precipitation in these two wetlands on a millennial time scale. However, with the different responses to the contrasting hydrological conditions, the carbon accumulations at these two sites showed an in-phase patterns on a millennial time scale. Our results imply that the carbon accumulations at these two sites are mainly controlled by local hydrologic conditions. The wetlands in both southern and northern China were found to be expanding during the interval from 6 to 4 cal. ka BP (ka = kilo annum), as inferred by a higher total organic carbon (TOC) content. For the Mystery Interval (MI, from 17.5 to 14.5 cal. ka BP), however, both hydrological conditions and carbon accumulations at these two sites showed an in-phase pattern.